Scolecite as an efficient heterogeneous catalyst for the synthesis of 2,4,5-triarylimidazoles - Gadekar, Lakshman S.; Mane, Shivshankar R.; Katkar, Santosh S.; Arbad, Balasaheb R.; Lande, Machhindra K. (Central European Journal of Chemistry, 2009)
Natural scolecite has been found as an effective catalyst for the one-pot synthesis of 2,4,5-triarylimidazole derivatives via a three component reaction using benzil or benzoin, aldehydes and ammonium acetate. This method provides several advantages such as being environmentally benign, reusable, possessing high yields with increased variations of the substituents in the product and preparative simplicity.
Keywords: 2; 4; 5-Triarylimidazoles; heterogeneous catalyst; Three-component reaction

Scolecite catalyzed facile and efficient synthesis of polyhydroquinoline derivatives through hantzsch multi-component condensation - Gadekar, Lakshman S.; Katkar, Santosh S.; Mane, Shivshankar R.; Arbad, Balasaheb R.; Lande, Machhindra K. (Bulletin of the Korean Chemical Society, 2009)
A facile and efficient synthetic route has been developed for the polyhydroquinoline via four component reactions of aldehydes, dimedone, ethyl acetoacetate and ammonium acetate in the presence of catalytic amount of scolecite in ethanol at 70 degrees C through Hantzsch reaction. This method gives remarkable advantages such as simple work-up procedure. environmentally friendly, inexpensive, non-toxic and recyclable catalyst, shorter reaction time along with excellent yields
Keywords: heterogeneous catalyst; Multicomponent reaction; Polyhydroquinoline; Reusable catalyst

New approach for the synthesis of miktoarm star polymers through a combination of thiol-epoxy ``click'' chemistry and ATRP/Ring-opening polymerization techniques - Gadwal, Ikhlas; Wadgaonkar, Prakash P.; Ichake, Amol B.; Mane, Shivshankar R. (Journal of Polymer Science Part A-Polymer Chemistry, 2019)
A new approach was developed for synthesis of certain A(3)B(3)-type of double hydrophilic or amphiphilic miktoarm star polymers using a combination of ``grafting onto'' and ``grafting from'' methods. To achieve the synthesis of desired miktoarm star polymers, acetyl protected poly(ethylene glycol) (PEG) thiols (M-n = 550 and 2000 g mol(-1)) were utilized to generate A(3)-type of homoarm star polymers through an in situ protective group removal and a subsequent thiol-epoxy ``click'' reaction with a tris-epoxide core viz. 1,1,1-tris(4-hydroxyphenyl)ethane triglycidyl ether. The secondary hydroxyl groups generated adjacent to the core upon the thiol-epoxy reaction were esterified with alpha-bromoisobutyryl bromide to install atom transfer radical polymerization (ATRP) initiating sites. ATRP of N-isopropylacrylamide (NIPAM) using the three-arm star PEG polymer fitted with ATRP initiating sites adjacent to the core afforded A(3)B(3)-type of double hydrophilic (PEG)(3)[poly(N-isopropylacrylamide)] (PNIPAM)(3) miktoarm star polymers. Furthermore, the generated hydroxyl groups were directly used as initiator for ring-opening polymerization of epsilon-caprolactone to prepare A(3)B(3)-type of amphiphilic (PEG)(3)[poly(epsilon-caprolactone)](3) miktoarm star polymers. The double hydrophilic (PEG)(3)(PNIPAM)(3) miktoarm star polymers showed lower critical solution temperature around 34 degrees C. The preliminary transmission electron microscopy analysis indicated formation of self-assembly of (PEG)(3)(PNIPAM)(3) miktoarm star polymer in aqueous solution. (c) 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2019, 57, 146-156
Keywords: Atom transfer radical polymerization (ATRP); miktoarm star polymers; ring-opening polymerization (ROP); thermoresponsive; thiol-epoxy

Novel synthetic approach for designing metal-free, redox-active quinoxaline-benzimidazole-based organic polymers with high energy storage capacity - Salunkhe, Pravin S.; Patil, Yuvraj S.; Dhole, Indrajeet A.; Kalshetti, Basavraj S.; Patil, Vikas B.; Mane, Shivshankar R.; Ghanwat, Anil A. (New Journal of Chemistry, 2019)
New organic framework materials, namely, polyphenylquinoxaline (QOP) and polyphenylquinoxaline-benzimidazole (QOP-BOP) were designed using a high-temperature (>100 degrees C) polymerization reaction with different monomers, i.e., 2,5-bis-[(4-benzoylcarbonyl)phenyl]-3-4 diphenyl thiophene (BbcPDT), aromatic tetraamines and biphenyl dicarboxylic acid. The QOP-BOP copolymer exhibited specific capacitance (SC) of 305 F g(-1) at the current density of 2 A g(-1) and 88% retention of its initial specific capacitance after 1000 cycles, which resulted in good cyclic stability. This work establishes the first use of thiophene integrated with quinoxaline-benzimidazole units for energy storage applications and provides strategies for further developments in the performance of such conjugated materials. Cyclic voltammetry, charge-discharge and electrochemical impedance techniques were used to evaluate the electrochemical parameters, which demonstrated their potential in future energy storage devices.

Partially bio-based aromatic poly(ether sulfone)s bearing pendant furyl groups: synthesis, characterization and thermo-reversible cross-linking with a bismaleimide - Nagane, Samadhan S.; Kuhire, Sachin S.; Mane, Shivshankar R.; Wadgaonkar, Prakash P. (Polymer Chemistry, 2019)
A fully bio-based bisphenol bearing pendant furyl group, viz., 4,4'-(furan-2-ylmethylene) bis(2-methoxyphenol) (BPF) was synthesized by base-catalyzed condensation of furfural with guaiacol. New partially bio-based (co) poly(ether sulfone) s bearing pendant furyl groups were synthesized via aromatic nucleophilic substitution polycondensation of BPF and various mixtures of BPF and bisphenol-A with bis(4-fluorophenyl) sulfone in N, N-dimethylacetamide as a solvent. (Co) poly(ether sulfone) s showed inherent viscosities in the range 0.92-1.47 dL g(-1) and number average molecular weights ((M-n) over bar), obtained from GPC, were in the range 91 300-131 000 g mol(-1). (Co) poly(ether sulfone) s could be cast into tough, transparent and flexible films from chloroform solutions. (Co)poly(ether sulfone)s showed 10% weight loss in the temperature range 431-481 degrees C and DSC showed T-g in the range 179-190 degrees C. Tensile strength, Young's modulus and elongation at break, obtained from tensile testing of (co) poly(ether sulfone) s containing pendant furyl groups, were in the range 76.7-83.8 MPa, 1.02-1.18 GPa and 21.4-89.7%, respectively. Most interestingly, pendant furyl groups in (co) poly(ether sulfone) s provide reactive sites for click modification and cross-linking via Diels-Alder reaction with maleimides and bismaleimides, respectively. Crosslinked (co) poly(ether sulfone) was prepared via Diels-Alder reaction of a representative (co) poly(ether sulfone) containing pendant furyl groups with 1,1'-(methylenedi-1,4-phenylene) bismaleimide (BMI) at 60 degrees C. The formation of cross-linked poly(ether sulfone) was demonstrated by gelation tests, solubility tests and DSC. The cross-linked copoly(ether sulfone) prepared using BMI showed enhanced tensile strength and Young's modulus compared to parent copoly(ether sulfone) and was recycled two times with retention of mechanical properties.

Trending methods employed for polymerization induced self-assembly - Mane, Shivshankar R. (New Journal of Chemistry, 2020)
Mother Nature produces a perfectly defined architecture that inspires researchers to make polymeric macromolecules for an array of functions. Preparation of a pre-defined polymer architecture is a key challenge to a researcher. The present article describes the recent development in Polymerization Induced Self-Assembly (PISA) to synthesize polymeric nanoparticles with pre-defined morphology and precise control over size and shape. This methodology has become a potential strategy for the synthesis of various block copolymer nano-objects. The PISA strategy produces core-shell polymeric nanoparticles with a wide scope of morphologies including spheres, worms, rods, and vesicles. A few parameters including the degree of polymerization, core-forming monomers, macro-CTA and solid content of the final product are precisely employed for the PISA procedure to accomplish the ideal size and shape. PISA opens a new avenue for the production of polymeric nano-objects.

Facile access to functional polyacrylates with dual stimuli response and tunable surface hydrophobicity - Mohammad, Sk Arif; Dolui, Subrata; Kumar, Devendra; Mane, Shivshankar R.; Banerjee, Sanjib (Polymer Chemistry, 2021)
Magnetically separable and reusable Ni-Co alloy nanoparticles were employed to achieve ambient temperature reversible deactivation radical polymerization (RDRP) of methyl acrylate (MA), for the first time, yielding well-defined PMA (at least up to 124 500 g mol(-1)) with a low dispersity (D <= 1.20). The controlled polymerization character of RDRP of MA was confirmed from the linear semilogarithmic plot exhibiting pseudo first order kinetics, a linear increase of the molecular weight of the polymer with monomer conversion maintaining low D and the synthesis of PMAs of varying molecular weights from 2200 to 124 500 g mol(-1) with low D. In addition, linear PMA-Br was used as a macroinitiator for the synthesis of several well-defined PMA-b-poly(M) block copolymers (where ``M'' stands for (2-dimethylamino)ethyl methacrylate (DMAEMA), tert-butyl methylacrylate (TBMA) and 2,2,3,3,4,4,5,5-octafluoropentyl acrylate (OFPA)), with acceptable Ds (<= 1.24), demonstrating the high chain-end fidelity of the macroinitiator. The synthesized PMA-b-PDMAEMA demonstrated dual pH- and thermo-responsive properties. Upon hydrolysis, the synthesized PMA-b-PTBMA leads to the formation of unprecedented carboxylic acid-functionalized PMA derivatives. PMA-b-POFPA copolymers with varying OFPA mol% in the copolymer led to polymers with tunable surface hydrophobicity, as revealed by the water contact angle measurements.

L-Histidine-derived smart antifouling biohybrid with multistimuli responsivity - Mohammad, Sk Arif; Dolui, Subrata; Kumar, Devendra; Mane, Shivshankar R.; Banerjee, Sanjib (Biomacromolecules, 2021)
A novel dual pH/thermoresponsive amphiphilic poly(histidine methacrylamide)-block-hydroxyl-terminated polybutadiene-block-poly(histidine methacrylamide) (PHisMAM-b-PB-b-PHisMAM) triblock copolymer biohybrid, composed of hydrophobic PB and ampholytic PHisMAM segments, is developed via direct switching from living anionic polymerization to recyclable nanoparticle catalyst-mediated reversible-deactivation radical polymerization (RDRP). The transformation involved in situ postpolymerization modification of living polybutadiene-based carbanionic species, end-capped with ethylene oxide, into dihydroxyl-terminated polybutadiene and a subsequent reaction with 2-bromo-2-methylpropionyl bromide resulting in a telechelic ATRP macroinitiator (Br-PB-Br). Br-PB-Br was used to mediate RDRP of an L-histidine-derived monomer, HisMAM, yielding a series of PHisMAM-b-PB-b-PHisMAM triblock copolymers. The copolymer's stimuli response was assessed against pH and temperature changes. The copolymer is capable of switching among its zwitterionic, anionic, and cationic forms and exhibited unique antifouling properties in its zwitterionic form. These novel triblock copolymers are expected to be show promising potential in biomedical applications.

Amino acid-derived ABCBA-type antifouling biohybrid with multi-stimuli responsivity and contaminant removal capability - Kumar, Devendra; Mohammad, Sk Arif; Kumar, Anand; Mane, Shivshankar R.; Banerjee, Sanjib (Polymer Chemistry, 2022)
Multi-stimuli (pH/thermo/redox)-responsive amphiphilic poly(cysteine methacrylamide)-block-poly(2-(dimethylamino)ethyl methacrylate)-block-polybutadiene-block-poly(2-(dimethylamino)ethyl methacrylate)-block-poly(cysteine methacrylamide) (PCysMAM-b-PDMAEMA-b-PB-b-PDMAEMA-b-PCysMAM) pentablock copolymer biohybrids, based on hydrophobic PB, ampholytic redox responsive PCysMAM and dual (pH and temperature) stimuli responsive PDMAEMA segments, are synthesized via a four-step synthesis protocol. The synthesis protocol involves: (1) in situ post polymerization modification of living polybutadiene-based carbanionic species to prepare hydroxyl terminated polybutadiene (HTPB); (2) introduction of an initiating functionality (capable of acting as an ATRP initiator) to HTPB, yielding a telechelic ATRP macroinitiator (Br-PB-Br); (3) recyclable alloy-mediated successive RDRP of DMAEMA and CysMAM, yielding a series of PCysMAM-b-PDMAEMA-b-PB-b-PDMAEMA-b-PCysMAM (A-B-C-B-A) pentablock copolymers with various chain lengths; and (4) conversion of the PDMAEMA block to poly(quaternary ammonium) (PQA) via quaternization. The stimuli responsiveness of the copolymer is investigated against changes in pH, temperature and redox. The pentablock copolymer self-assembles into spherical nanospheres, can switch between its monocationic, zwitterionic and monoanionic charged states, exhibits antifouling behaviour and is capable of removing ionic contaminants from water. These pentablock copolymers may emerge as a promising material for emerging applications.